2018
DOI: 10.1128/jvi.01025-18
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Strategy for a Quadrivalent Live Attenuated Influenza Virus Vaccine

Abstract: Seasonal influenza viruses infect 1 billion people worldwide and are associated with ∼500,000 deaths annually. In addition, the never-ending emergence of zoonotic influenza viruses associated with lethal human infections and of pandemic concern calls for the development of better vaccines and/or vaccination strategies against influenza virus. Regardless of the strategy, novel influenza virus vaccines must aim at providing protection against both seasonal influenza A and B viruses. In this study, we tested an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 41 publications
(47 reference statements)
3
18
0
Order By: Relevance
“…In contrast, PBS-vaccinated/challenged mice showed severe body weight loss. Only one female (out of 8) and none of the male mice survived in the PBS-vaccinated/challenged group, consistent with previous studies [27,31]. (C) Post-challenge antibody titer determination.…”
Section: Qualitative Differences In Humoral Responses Among Different Vaccine Groupssupporting
confidence: 89%
See 2 more Smart Citations
“…In contrast, PBS-vaccinated/challenged mice showed severe body weight loss. Only one female (out of 8) and none of the male mice survived in the PBS-vaccinated/challenged group, consistent with previous studies [27,31]. (C) Post-challenge antibody titer determination.…”
Section: Qualitative Differences In Humoral Responses Among Different Vaccine Groupssupporting
confidence: 89%
“…Live attenuated vaccine platforms have been among the most explored over the years (reviewed in [24]). In addition to the coldadapted LAIVs developed in the 60's that form the basis of the current LAIVs approved for human use, alternative LAIV approaches have been developed that include modifications and deletions to the NS1 gene segment, generation of M2 deficient viruses, alternative virus backbones with temperature sensitive phenotypes, among others [25][26][27][28][29][30][31]. We have previously shown that genome re-arrangement is a suitable strategy for the development of influenza A virus LAIVs [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have developed a LAIV strategy by incorporating ts mutations on the PB1 that can be applied similarly for both IAV and IBV [19,21,22]. This strategy has been shown to be safe and effective in mice, pigs and chickens, stimulating cross-protective immunity against antigenically distinct viruses and can be used in a quadrivalent formulation [19,20,22,[30][31][32]. In a previous study using an IBV LAIV candidate with the PB1 gene segment carrying three ts mutations K391E, E580G, S660A and a C-terminus HA tag, the K391E mutation reverted to its wild type form (E391K) during the initial passages in SPF eggs [22].…”
Section: Discussionmentioning
confidence: 99%
“…Influenza vaccine is the recommended approach to protect against influenza virus infection. Currently, influenza vaccines approved by the US FDA include inactivated influenza vaccine (IIV), recombinant influenza protein (RIP), and live attenuated influenza vaccine (LAIV) [1]. Studies have shown that inactivated influenza virus vaccine is wildly used and shows good safety and immunogenicity after immunization in humans [2][3][4].…”
Section: Introductionmentioning
confidence: 99%